Comprehensive phylogeny of Konosirus punctatus (Clupeiformes: Clupeidae) based on transcriptomic data. Issue 5 (28th May 2021) - Lou, Fangrui; Qiu, Shengyao; Tang, Yongzheng; Wang, Zhiyang; Wang, Lei
Abstract: Konosirus punctatus is an important species for the structure of marine ecosystems. Meanwhile, it is a native species in the northwest Pacific Ocean and supports important commercial fishery. In the present study, we generated the whole transcriptome of K. punctatus from combined tissues (muscle, liver, gill, heart, kidney, swim bladder and sexual gland) using Illumina RNA-seq technology and a total of 46087110 clean reads were obtained, corresponding to 6531521430 nucleotides. Meanwhile, 10000 clean reads were randomly selected and compared with NT database to examine the possible contamination. Results showed that 6754 clean reads were distributed among some species closely related with K. punctatus, indicating no-pollution. De novo assembly was performed and all clean reads were assembled to produce 71610 longest unigenes with an N50 of 906 bp. Among all the unigenes, 43974 unigenes were annotated in at least one database and 3172 unigenes were annotated in all databases. All unigenes were further analyzed to predict the gene structure and we have obtained a total of 54864 coding sequences (CDSs) and 17326 simple sequence repeats (SSRs). Saturation analyses were applied to evaluate the accuracy of gene expression and we hypothesized that the detection of gene expression might be effective. Finally, single-copy orthologous genes were applied to construct the phylogenetic relationship of K. punctatus . Results showed that K. punctatus diverged from the common ancestor with Alosa alosa, Alosa pseudoharengus and Sardina pilchardus at approx. 61.16–92.52 MYA. The present study will provide a foundational molecular information for the biological research of K. punctatus .